Three scenarios for the development of the Sisi regime in Egypt: Development dictatorship, Mubarak 2.0, or rapid collapse? - Luca Miehe; Stephan Roll (Stiftung Wissenschaft und Politik (SWP), 2019)
A referendum on a constitutional amendment is to be held in Egypt at the beginning of May, which would enable President Abdel-Fatah al-Sisi to continue governing after the end of his current term. In the face of massive repression, approval seems certain. This would largely complete the power consolidation of the Sisi-regime, which emerged from the military coup of July 2013. But how will this regime develop in the future? Possible scenarios are a successful development dictatorship, decades of political and economic stagnation, as under Hosni Mubarak, or imminent failure. While a development dictatorship is unrealistic due to a lack of willingness to reform, the other two scenarios entail major risks for Germany and its European partners. In the future, they should therefore link new budgetary assistance to improvements in human and civil rights, focus on humanitarian crisis prevention in line with the 'do no harm' approach, and expand contacts with representatives of the Egyptian opposition outside of Egypt.
Keywords: 320